THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND READING COMPREHENSION ACHIEVEMENT - Sihabudin; Darojatul Romli, Asep; Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
The objective of English teaching at university is the ability to read English. But in the reality, so many students are not able to write. Commonly they only have capability in listening, speaking and speaking. We can find this problem in almost all English classes. Reading, although it is a complicated skill, is definitely a skill that the language teacher must teach to their students. Reading is very important since it is a process of building and sharing meaning through the usage of verbal and non-verbal symbols Moreover, teaching reading should improve students’ communicative skills and learn how to use the language However, reading in English is still a problem for most Indonesian students although they have studied English from the elementary school. Only a few of them have good ability in reading. Based on the output of the research in realization about students’ vocabulary mastery is taken from multiple choice tests. This text has 30 items the pupils are given test at last lesson. After doing the span calculation, standard deviation so the result are the best score is 27 and the worst score is 16. The mark of students by researcher is grouped to be classes, the length of the class is 2 and the first interval class is 16-17, so it could be made frequency distribution about students’ vocabulary mastery which is made sample in research. There is significant positive correlation between variable of students’ vocabulary mastery (X) with variable of students’ reading comprehension (Y). it is shown by r – count is the bigger than r – table on significant degree 0,05 and N as many as 30 (0,577 > 0,361). Students’ reading comprehension which has good category is as many as 9 or 30%. The students’ reading comprehension which has middle category is as many as 11 or 36,7% and the students’ reading comprehension which has bad category is as many as 8 or 26,6%. To be clearer,